SOCIAL ENGAGEMENT AND PSYCHOLOGICAL DISTRESS IN INSTITUTIONALIZED OLDER ADULTS: A MEDIATING ROLE OF LONELINESS - Khan, Mishal; Mahmood , Zahid (Journal of Postgraduate Medical Institute, 2024)
Objective: To explore the mediating role of loneliness in social engagement and psychological distress in institutionalized older adults. Methodology: This cross-sectional study was conducted at six government and private old age institutions in Lahore, from November, 2019 to February, 2020. The data was selected through purposive sampling technique and comprised of 100 older adults aged between 65-80 years residing in old age homes for more than 6 months. Data was collected using Lubben Social Networking Scale, Loneliness Scale and Depression, Anxiety and Stress Scale. Results: The overall mean age was 73.46±6.91 years. A significant negative association between social engagement, loneliness and psychological distress (p<0.001), and a significant positive association between loneliness (p<0.001) and psychological distress (p<0.01) was found. Loneliness fully mediated the relationship between social engagement and psychological distress (p < 0.001). Conclusion: Reducing social disengagement experienced by institutionalized older adults could reduce feelings of loneliness and consequently psychological distress experienced by them.